PENERAPAN REVIEW KRITIS ARTIKEL ILMIAH DALAM PERKULIAHAN METODOLOGI PENELITIAN - Setyo Eko Atmojo; Beny Dwi Lukitoaji (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The purpose of this study was to improve the mastery of the concept of research methodology in undergraduate students of elementary school teacher education, the Faculty of Teacher Training and Education, Universitas PGRI Yogyakarta. This research method is a classroom action research which consists of two cycles where each cycle consists of four meetings. The subjects of this study were students of semester VI class A3-17 consisting of 40 students. This research was conducted in the even semester of 2019/2020 from February 2020 to March 2020. The results showed mastery of the concept of research methodology where> 80% of students mastered the concept of research methodology well. In addition,> 80% of students responded positively to learning and 36 out of 40 students received good and excellent scores in the assessment of research proposals as the final product of the research methodology course. Keywords: Critical Review, Scientific Articles, Research Methodology Concept